Apuntes de medicina desportiva (Fiep Bulletin - online, 2015)
Present day sports performances lead athletes systems to the limit of their physiological possibilities, which require certain adaptations, specially a reciprocal conditioning of motor and visceral functions related to excitability, metabolism and trophism.